WebLab SOA no Domínio de Redes de Computadores para Experimentos DiffServ - Rocha, Lucio Agostinho (2009)
This work presents a remote laboratory (WebLab) for practical teaching of Computer Networks discipline with the use of experiments related to DiffServ technology. It is proposed a implementation of DiffServ architecture and its evaluation in the laboratory. TheWebLab implementation follows the Services Oriented Architecture (SOA) and uses the Service Oriented Computing (SOC) paradigm through experiments to realize Web Services composition. The experiments includes monitoring of flows submission at domain and the stablishing of management intra-domain using a Bandwidth Broker. The work also provides a viable and safe software infrastructure for administrative and use management of experiments in WebLabs.